Empowering Village Administrators in Preventing Disputes Through Basic Paralegal Training in Apuan Village, Susut District, Bangli Regency - I Nyoman Gede Sugiartha; A.A Sagung Laksmi Dewi; Ni Made Sukaryati Karma; I Wayan Sunarta; Ayu Prasetya Dewi; I Gusti Agung Ayu Candra Nigrat (Fakultas Hukum, Universitas Warmadewa, 2023)
Cases or disputes are common in both urban areas and rural areas. The existence of differences in interests causes disputes to occur both in the private sphere and in the public sphere. Likewise, in Apuan Village, small clashes often occur which sometimes cause disharmony in society. The importance of understanding community law and village officials will greatly help defuse and resolve disputes that arise in the community. The purpose of this research is to provide basic paralegal training to village officials to prevent disputes from occurring. The implementation method is by conducting interviews with the Apuan Village Government. This can happen due to the lack of public knowledge, especially the poor and marginal people about the law. Paralegal arrangements have been regulated in Law Number 16 of 2011 concerning Legal Aid and Regulation of the Minister of Law and Human Rights Number 3 of 2021 concerning Paralegals in Providing Legal Aid. very important socialized to the village level. As a follow-up step, it is necessary to provide basic paralegal knowledge for village officials as a protector of the community if there is a dispute in the community.